2013
DOI: 10.4236/ojvm.2013.31012
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Seeds By-Product as Protein Source for Piglets

Abstract: Tobacco seed cake is a by-product with interesting characteristics for animal nutrition, due to its high protein content. The focus of this study is to evaluate if tobacco seed cake, administered in feed, can affect principal serum metabolic parameters of weaned piglets in order to establish if it can be used as both a delivery system of edible vaccines and an alternative protein source in piglets diet. A total of 48 weaned piglets were divided in two homogeneous groups for weight, control (CG) and treatment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Moreover, the re-sprouting from the stump after threshing makes multiple seed harvests (up to three times a year) possible for this variety in optimal environmental/ agronomical conditions. By cold pressing, Solaris seeds produce 33 % of oil and the residual 67 % can be used for a protein cake (Fogher et al 2011;Rossi et al 2013). In addition, a significant quantity of capsules previously separated from seeds and the remaining green tissues (stems and leaves) in the field can be collected for biomass production.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the re-sprouting from the stump after threshing makes multiple seed harvests (up to three times a year) possible for this variety in optimal environmental/ agronomical conditions. By cold pressing, Solaris seeds produce 33 % of oil and the residual 67 % can be used for a protein cake (Fogher et al 2011;Rossi et al 2013). In addition, a significant quantity of capsules previously separated from seeds and the remaining green tissues (stems and leaves) in the field can be collected for biomass production.…”
Section: Introductionmentioning
confidence: 99%
“…This encapsulation offers the potential for the antigen to be protected against rapid and complete degradation and to be gradually released as host tissues are digested (Rossi et al, 2011). As previously discussed, the inclusion of tobacco seeds in the piglet diet was able to cover the nutritional requirements without affecting growth, feed efficiency and metabolic parameters and can thus be used as a protein source (Rossi et al, 2013b). In order to reduce the volume of vaccine seeds, tobacco seed cake obtained through cold pressing can be used, which would be an effective way to obtain a higher concentration of heterologous proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that tobacco seeds, which have less than 2 µg/kg of nicotine, can be integrated into livestock feeding without affecting the palatability (Rossi et al, 2007) or metabolic parameters. A recent study showed that tobacco seed cake, a by-product obtained after oil extraction, could be used as a cost-effective protein source in piglet nutrition (Rossi et al, 2013b). It is also included in the EU feed material register (number 00753-IT).…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco seeds in particular have the potential to be used in the production of biodiesel, edible oil, food and feed mixes, and other products [5][6][7], as they contain various nutrient and bioactive metabolites, and are nicotine-free. Tobacco seeds of various genotypes have been found to contain about 30-49% glyceride oil (with palmitic, oleic and linoleic acids being the dominant fatty acids), 0.3-1.7% phospholipids (phosphatidylinositol, phosphatidylcholine, and phosphatidylethanolamine as the primary components), 0.3-0.8% sterols (mainly β-sitosterol, stigmasterol and campesterol), 2-195 mg.kg −1 tocopherols (mainly γ-tocopherol), 18-41% protein (rich in essential amino acids), 3.5-21.8% fiber, macro and micro minerals (K, Mg, Na, Zn, Cu), and other valuable nutrients [5,6,[8][9][10][11][12][13][14][15]. The tiny tobacco seeds, 10000-16000 units in a gram, constitute about 3.7% of the plant biomass in Oriental tobacco, thus providing an average yield of about 300 kg/ha [16,17].…”
Section: Introductionmentioning
confidence: 99%